A wireless inertial measuring system for human motion analysis - Qi, Minhui; Li, Yuping; Xiang, Kui; Ge, Yunjian (2016 IEEE International Conference on Information and Automation (ICIA), 2016)
A wireless inertial measuring system is designed for human motion analysis in this study. Each of the measurement unit bonded at the human joint consists of a three-axis accelerometer, magnetometer and gyroscope. A wireless body sensor network based on Wi-Fi is built to collect all the information of the measurement units and transfer to the computer in real time. An orientation estimation algorithm presented by quaternion is used to calculate the gyroscope measurement error by using accelerometer and magnetometer data. The motion data are imported into a type of simulation software, Virtual Robot Experimentation Platform (V-REP), to reconstruct the human motion posture. In a simple experiment, the measurement units are fixed on human's lower limbs and the motion data are sampled to update the model in V-REP. The system developed in this study is important to the gait analysis, locomotion control and visual feedback in rehabilitation.